Influence of physiological and supraphysiological hyperinsulinemia on skin microcirculation in healthy volunteers - Krčma, Michal (Baishideng Publishing Group Co., Limited, 2013)
AIM: To examine skin perfusion in dependency on insulinemia in healthy subjects. METHODS: All volunteers were informed in detail about the procedures and signed informed consent. The protocol of this study was approved by the ethical committee. In our study, a two stage hyperinsulinemic euglycemic clamp was performed, with insulinemia 100 and 250 mIU/mL and glycemia 5.0 mmol/L (3% standard deviation). Before the clamp and in steady states, microcirculation was measured by laser Doppler flowmetry and transcutaneous oximetry and energy expenditure was measured by indirect calorimetry. Results (average and standard deviation) were evaluated with paired t-test. RESULTS: Physiological (50 mIU/L) insulinemia led to higher perfusion in both tests; hyperemia after heating to 44%-1848% (984-2046) vs 1599% (801-1836), P < 0.05, half time of reaching peak perfusion after occlusion release 1.2 s (0.9-2.6) vs 4.9 s (1.8-11.4), P < 0.05. Supraphysiological (150 mIU/L) insulinemia led to even higher perfusion in both tests; hyperemia after heating to 44%-1937% (1177-2488) vs 1599% (801-1836), P < 0.005, half time to reach peak perfusion after occlusion release 1.0 s (0.7-1.1) vs 4.9 s (1.8-11.4), P < 0.005. A statistically significant increase occurred in tissue oxygenation in both insulinemia. The difference in perfusion and oxygenation between physiological and supraphysiological hyperinsulinemia was not statistically significant. CONCLUSION: The post occlusive hyperemia test in accordance with heating test showed significantly increasing skin perfusion in the course of artificial hyperinsulinemia. This effect rises non-linearly with increasing insulinemia. Dependency on the dose was not statistically significant.